No long-term evidence of hyporesponsiveness after use of pneumococcal conjugate vaccine in children previously immunized with pneumococcal polysaccharide vaccine - Licciardi, P; Toh, Z; Clutterbuck, E; Balloch, A; Marimla, R; Tikkanen, L; Lamb, K; Bright, K; Rabuatoka, U; Tikoduadua, L; Boelsen, L; Dunne, E; et al. (Elsevier, 2016)
Background: A randomized controlled trial in Fiji examined the immunogenicity and effect on nasopharyngeal carriage after 0, 1, 2, or 3 doses of 7-valent pneumococcal conjugate vaccine (PCV7; Prevnar) in infancy followed by 23-valent pneumococcal polysaccharide vaccine (23vPPV; Pneumovax) at 12 months of age. At 18 months of age, children given 23vPPV exhibited immune hyporesponsiveness to a micro-23vPPV (20%) challenge dose in terms of serotype-specific IgG and opsonophagocytosis, while 23vPPV had no effect on vaccine-type carriage. Objective: This follow-up study examined the long-term effect of the 12-month 23vPPV dose by evaluating the immune response to 13-valent pneumococcal conjugate vaccine (PCV13) administration 4 to 5 years later. Methods: Blood samples from 194 children (now 5-7 years old) were taken before and 28 days after PCV13 booster immunization. Nasopharyngeal swabs were taken before PCV13 immunization. We measured levels of serotype-specific IgG to all 13 vaccine serotypes, opsonophagocytosis for 8 vaccine serotypes, and memory B-cell responses for 18 serotypes before and after PCV13 immunization. Results: Paired samples were obtained from 185 children. There were no significant differences in the serotype-specific IgG, opsonophagocytosis, or memory B-cell response at either time point between children who did or did not receive 23vPPV at 12 months of age. Nasopharyngeal carriage of PCV7 and 23vPPV serotypes was similar among the groups. Priming with 1, 2, or 3 PCV7 doses during infancy did not affect serotype-specific immunity or carriage. Conclusion: Immune hyporesponsiveness induced by 23vPPV in toddlers does not appear to be sustained among preschool children in this context and does not affect the pneumococcal carriage rate in this age group.